PENGARUH GAYA KEPEMIMPINAN TERHADAP KETERLIBATAN KARYAWAN DI PERUSAHAAN TEKNOLOGI - Sakti P Sihombing; Nia Ramadani; Febyla Bisatrio Adhel; Maria Devlina; Yeremia Prayogi (Prosiding SEMANIS: Seminar Manajemen Bisnis, 2024)
This research aims to investigate the influence of leadership styles on employee engagement in technology companies. In the context of a dynamic and innovative business environment, effective leadership is considered crucial to enhance employee engagement, which, in turn, can positively impact organizational performance. The study will focus on various leadership styles, such as transformational, transactional, and authoritarian, to identify the relationship between the applied leadership styles and the level of employee engagement. The research methodology involves a survey using a randomly selected sample of employees from technology companies. The collected data will be analyzed using statistical techniques, such as linear regression, to assess the extent to which leadership style variables affect employee engagement variables. Furthermore, the research will explore specific aspects of leadership styles that have a significant impact on employee engagement, providing deeper insights for leaders and management in technology companies. The findings from this research are expected to contribute to both practical and theoretical understanding of the importance of leadership styles in creating a motivating and engaging work environment for employees in technology companies. The managerial implications of the research findings can assist organizational leaders in identifying areas that need strengthening in their leadership practices to enhance employee engagement and performance. Additionally, this research may lay the foundation for further studies in the fields of leadership and human resource management